Preparation method of titanium-oxygen coordination material, titanium-oxygen coordination material and application

CN116143825BActive Publication Date: 2026-10-30UNIV OF SCI & TECH OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310153557.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-17
Publication Date
2026-10-30
Estimated Expiration
2043-02-17

AI Technical Summary

Technical Problem

但是该简单组合结构单一,功能扩展困难,材料中活性位点的化学环境和空间特性的调控因素和范围极为有限

Benefits of technology

[0014]本发明另一方面提供了一种钛氧配位材料,该钛氧配位材料是通过上述制备方法制备得到的。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116143825B_ABST
    Figure CN116143825B_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a titanium-oxygen coordination material, the titanium-oxygen coordination material and application. The preparation method comprises the following steps: mixing a solid titanium-containing compound precursor, an organic ligand and an acidic aqueous solution according to a preset ratio to obtain a mixed reaction system; and the mixed reaction system is reacted under a preset condition to generate the titanium-oxygen coordination material; wherein the structure of the titanium-oxygen coordination material comprises zero dimension to three dimensions; the molar ratio of the solid titanium-containing compound precursor to the organic ligand is 1:3-3:1; and the preset condition comprises the following: the reaction concentration is 0.1-5 mmol / mL; and the reaction time is 2-72 h.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coordination materials technology, specifically to a method for preparing titanium-oxygen coordination materials, the titanium-oxygen coordination materials themselves, and their applications. Background Technology

[0002] Titanium oxide materials, represented by titanium dioxide, exhibit significant application prospects in fields such as new energy, life sciences, environmental protection, and sustainable development due to their unique photoelectric response properties and excellent biocompatibility. Therefore, developing new synthetic methods and technologies for next-generation titanium oxide materials to achieve systematic regulation of their structure and properties, in response to the needs of the new materials industry, is a crucial link in the research and industrial application of this field and is of paramount importance.

[0003] Conventional titanium dioxide compounds, due to their dense crystal structure and lack of accessible pores, have a limited number of active sites, which severely restricts the types and diffusion rates of functional guest molecules, significantly hindering further improvements in their photoelectric response performance. To address this critical issue, various technical strategies have emerged. For example, template synthesis methods can be used to directly introduce pores (micropores, mesopores, macropores, and hierarchical pores) into the titanium dioxide structure, or the morphology and size of titanium dioxide particles can be controlled, resulting in a significant increase in specific surface area and alteration of photoelectric response performance. However, these materials lack a long-range ordered and accurate crystal structure, exhibiting poor crystallinity, making it difficult to identify active sites, clarifying structure-activity relationships, and resulting in low reproducibility stability. Therefore, to clarify structure-activity relationships and improve reproducibility stability, developing crystalline titanium oxide cluster compounds with accurate atomic-level crystal structures has become an important solution.

[0004] Currently, simple fatty alcohols (methanol, ethanol, isopropanol, etc.), hydroxyl groups (-OH), and negative oxygen ions (oxo, O) are utilized. 2- ) groups and inorganic acid radicals (SO4) 2- PO4 3- The combination of these compounds with titanium ions can construct single-crystal titanium oxide cluster compounds with abundant metal nuclei and molecular cage size and shape, thus achieving a certain degree of simulation of the titanium dioxide structure and regulation of related properties. However, this simple combination has a single structure, difficulty in functional expansion, and extremely limited control over the chemical environment and spatial characteristics of active sites in the material. Summary of the Invention

[0005] In view of this, the present invention provides a method for preparing a titanium-oxygen coordination material and a titanium-oxygen coordination material, wherein the prepared titanium-oxygen coordination material has high crystallinity and superior chemical stability.

[0006] To achieve the above objectives, the present invention provides a method for preparing titanium-oxygen coordination materials. The method includes: mixing a solid titanium-containing compound precursor, an organic ligand, and an acidic aqueous solution in a predetermined ratio to obtain a mixed reaction system; reacting the mixed reaction system under predetermined conditions to generate a titanium-oxygen coordination material; wherein the structure of the titanium-oxygen coordination material ranges from zero-dimensional to three-dimensional; the molar ratio of the solid titanium-containing compound precursor to the organic ligand is 1:3 to 3:1; the predetermined conditions include: a reaction concentration of 0.1 to 5 mmol / mL; and a reaction time of 2 to 72 h.

[0007] According to an embodiment of the present invention, the solid titanium-containing compound precursor is a solid titanium-containing elemental compound, which includes one of the following: elemental titanium, titanium oxide, titanium carbide, titanium nitride, titanium fluoride, titanium-containing complex salt, or titanium complex.

[0008] According to an embodiment of the present invention, the acidic aqueous solution is formed by mixing an acid activator with water; the acid activator includes inorganic acids and organic acids, the inorganic acids including at least one of the following: hydrochloric acid, sulfuric acid, nitric acid or phosphoric acid, etc., and the organic acids including at least one of the following: formic acid, acetic acid, oxalic acid, sulfonic acid or phosphorous acid, etc.

[0009] According to an embodiment of the present invention, the molar ratio of the solid titanium-containing compound precursor to the acid activator is 1:1 to 1:50.

[0010] According to an embodiment of the present invention, the reaction process in which the mixed reaction system reacts under preset conditions includes: activation and slow release of titanium ions in the mixed reaction system, coordination of titanium ions with organic ligands, and crystal growth of titanium-oxygen coordination products.

[0011] According to an embodiment of the present invention, the preset conditions further include a reaction temperature, which is room temperature to 200°C.

[0012] According to embodiments of the present invention, the organic ligand is an organic compound having two or more oxygen coordination sites.

[0013] According to embodiments of the present invention, the structural parent of the organic ligand includes at least one of the following: aliphatic chain, aliphatic ring, aromatic hydrocarbon, spirocyclic ring, bridged ring, or fused ring; the coordinating group of the organic ligand includes at least one of the following: carboxyl group, hydroxyl group, sulfonic acid group, phosphite group, aldehyde group, or combinations thereof.

[0014] In another aspect, the present invention provides a titanium-oxygen coordination material, which is prepared by the above-described preparation method.

[0015] In another aspect, the present invention provides the application of titanium-oxygen coordination materials in the fields of mixture adsorption and separation, catalysis, guest storage, proton conduction, response to external stimuli, and biomedicine.

[0016] According to embodiments of the present invention, by using water as the synthesis solvent and a solid titanium-containing compound precursor as the metal source, the titanium precursor is activated in situ with acids. An unconventional high-concentration reaction is employed to prevent the hydrolysis of titanium ions, control the reaction rate, promote the formation of titanium-oxygen coordination materials, and balance the hydrolysis and coordination processes of titanium ions. This addresses the limitations of the controllable range of chemical environment and spatial characteristics of the active sites in the material, as well as the technical problem of difficulty in reaction control due to the high reactivity and complexity of titanium ions in solution during the preparation of traditional titanium-oxygen coordination materials, which leads to the formation of titanium dioxide precipitates and thus prevents the synthesis of highly crystalline titanium-oxygen coordination materials. This method achieves the preparation of novel titanium-oxygen coordination materials with high crystalline properties and superior chemical stability. Furthermore, the synergistic effect between each process of titanium-oxygen coordination is controlled by varying the reaction temperature, reaction time, and molar ratio of the composition, simultaneously achieving the synthesis of novel titanium-oxygen coordination materials from both thermodynamic and kinetic perspectives, demonstrating the universality of this preparation method. Attached Figure Description

[0017] Figure 1 A flowchart illustrating a method for preparing titanium-oxygen coordination materials according to an embodiment of the present invention is shown schematically.

[0018] Figure 2(a) schematically illustrates the structure of an organic ligand according to an embodiment of the present invention;

[0019] Figure 2(b) schematically illustrates the structure of an organic ligand exemplified in an embodiment of the present invention;

[0020] Figure 3(a) schematically shows a schematic diagram of the inorganic component structural unit of the titanium-oxygen coordination material according to Embodiment 1 of the present invention;

[0021] Figure 3(b) schematically shows the structural diagram of the titanium-oxygen coordination material according to Embodiment 1 of the present invention;

[0022] Figure 3(c) schematically shows the powder X-ray diffraction pattern of the titanium-oxygen coordination material according to Embodiment 1 of the present invention;

[0023] Figure 3(d) schematically shows a scanning electron microscope image of the titanium-oxygen coordination material according to Embodiment 1 of the present invention;

[0024] Figure 3(e) schematically shows the thermogravimetric analysis diagram of the titanium-oxygen coordination material according to Embodiment 1 of the present invention;

[0025] Figure 3(f) schematically shows the carbon dioxide adsorption isotherm of the titanium-oxygen coordination material according to Embodiment 1 of the present invention;

[0026] Figure 4(a) schematically shows a schematic diagram of the inorganic component structural unit of the titanium-oxygen coordination material according to Embodiment 2 of the present invention;

[0027] Figure 4(b) schematically shows the structural diagram of the titanium-oxygen coordination material according to Embodiment 2 of the present invention;

[0028] Figure 4(c) schematically shows the powder X-ray diffraction pattern of the titanium-oxygen coordination material according to Embodiment 2 of the present invention;

[0029] Figure 4(d) schematically shows a scanning electron microscope image of the titanium-oxygen coordination material according to Embodiment 2 of the present invention;

[0030] Figure 4(e) schematically shows the thermogravimetric analysis diagram of the titanium-oxygen coordination material according to Embodiment 2 of the present invention;

[0031] Figure 4(f) schematically shows the carbon dioxide adsorption isotherm of the titanium-oxygen coordination material according to Embodiment 2 of the present invention;

[0032] Figure 5(a) schematically illustrates the inorganic component structural unit of the titanium-oxygen coordination material according to Embodiment 3 of the present invention;

[0033] Figure 5(b) schematically shows the structural diagram of the titanium-oxygen coordination material according to Embodiment 3 of the present invention;

[0034] Figure 5(c) schematically shows the powder X-ray diffraction pattern of the titanium-oxygen coordination material according to Embodiment 3 of the present invention;

[0035] Figure 5(d) schematically shows a scanning electron microscope image of the titanium-oxygen coordination material according to Embodiment 3 of the present invention;

[0036] Figure 5(e) schematically shows the thermogravimetric analysis diagram of the titanium-oxygen coordination material according to Embodiment 3 of the present invention;

[0037] Figure 5(f) schematically shows the carbon dioxide adsorption isotherm of the titanium-oxygen coordination material according to Embodiment 3 of the present invention;

[0038] Figure 6(a) schematically illustrates the inorganic component structural unit of the titanium-oxygen coordination material according to Embodiment 4 of the present invention;

[0039] Figure 6(b) schematically shows the structural diagram of the titanium-oxygen coordination material according to Embodiment 4 of the present invention;

[0040] Figure 6(c) schematically shows the powder X-ray diffraction pattern of the titanium-oxygen coordination material according to Embodiment 4 of the present invention;

[0041] Figure 6(d) schematically shows a scanning electron microscope image of the titanium-oxygen coordination material according to Embodiment 4 of the present invention;

[0042] Figure 6(e) schematically illustrates the thermogravimetric analysis of the titanium-oxygen coordination material according to Embodiment 4 of the present invention;

[0043] Figure 6(f) schematically shows the carbon dioxide adsorption isotherm of the titanium-oxygen coordination material according to Embodiment 4 of the present invention;

[0044] Figure 7(a) schematically illustrates the inorganic component structural unit of the titanium-oxygen coordination material according to Embodiment 5 of the present invention;

[0045] Figure 7(b) schematically illustrates the structure of the titanium-oxygen coordination material according to Embodiment 5 of the present invention;

[0046] Figure 7(c) schematically shows the powder X-ray diffraction pattern of the titanium-oxygen coordination material according to Embodiment 5 of the present invention;

[0047] Figure 7(d) schematically shows a scanning electron microscope image of the titanium-oxygen coordination material according to Embodiment 5 of the present invention;

[0048] Figure 7(e) schematically illustrates the thermogravimetric analysis of the titanium-oxygen coordination material according to Embodiment 5 of the present invention;

[0049] Figure 7(f) schematically shows the carbon dioxide adsorption isotherm of the titanium-oxygen coordination material according to Embodiment 5 of the present invention. Detailed Implementation

[0050] To make the objectives, technical solutions, and advantages of the present invention clearer, the present invention will be further described in detail below with reference to specific embodiments and accompanying drawings.

[0051] Because the factors and scope for regulating the chemical environment and spatial properties of active sites in titanium oxide materials are extremely limited, a development strategy for titanium oxide coordination materials has emerged. The introduction of organic ligands not only enriches the chemical environment surrounding the active sites in the material but also makes the confined space in the structure tunable, controllable, and variable.

[0052] In related technologies, the preparation of traditional titanium-oxygen coordination materials is difficult to control due to the high reactivity and complexity of titanium ions in solution. Titanium ions are easily hydrolyzed to form titanium dioxide precipitates. Therefore, the preparation of traditional titanium-oxygen coordination materials is mostly carried out on a scientific research scale in vacuum glove boxes, vacuum reactors, and sealed reaction vessels to achieve the requirements of anhydrousness and air isolation. Liquid precursors (TiCl4, Ti(iPrO)4) are used to assemble titanium ions with organic ligands in an anhydrous environment.

[0053] The above methods, on the one hand, cannot be further optimized for green mass production because they require anhydrous and air-isolated conditions; on the other hand, the synthesis parameters of known titanium-oxygen coordination materials have a narrow window of application and strict control, and the preparation methods lack universality and cannot be applied to different types of organic ligands and different types of material structures.

[0054] Based on this, the present invention provides a method for preparing titanium-oxygen coordination materials to achieve the preparation of titanium-oxygen coordination materials with high crystallinity and good chemical stability, while also achieving the universality of the preparation method.

[0055] Figure 1 A flowchart illustrating a method for preparing titanium-oxygen coordination materials according to an embodiment of the present invention is shown.

[0056] like Figure 1 As shown, the method may include operations S101 to S102.

[0057] In operation S101, a solid titanium-containing compound precursor, an organic ligand, and an acidic aqueous solution are mixed in a preset ratio to obtain a mixed reaction system.

[0058] In operation S102, the mixed reaction system reacts under preset conditions to generate titanium-oxygen coordination materials.

[0059] According to embodiments of the present invention, the solid titanium-containing compound precursor can be a solid titanium-containing elemental compound. The solid titanium-containing elemental compound can include one of the following: elemental titanium, titanium oxide, titanium carbide, titanium nitride, titanium fluoride, titanium-containing double salt, or titanium complex.

[0060] According to embodiments of the present invention, the solid titanium-containing compound precursors are all inert solid compounds that are insensitive to air and water and can be easily taken out in an air atmosphere; the organic ligands and acidic aqueous solutions also do not require deoxygenation, degassing and drying treatment.

[0061] According to embodiments of the present invention, the organic ligand can be an organic compound having two or more oxygen coordination sites. The parent structure of the organic ligand can include at least one of the following: aliphatic chain, aliphatic ring, aromatic hydrocarbon, spirocyclic ring, bridged ring, or fused ring; the coordinating group of the organic ligand includes at least one of the following: carboxyl group, hydroxyl group, sulfonic acid group, phosphite group, aldehyde group, or combinations thereof.

[0062] According to embodiments of the present invention, the organic ligand may include: squaric acid, gallic acid, 4,6-dihydroxyisophthalic acid, 1,2,4-benzenetricarboxylic acid, pyromellitic acid, etc.

[0063] For example, Figure 2(a) schematically shows a structural diagram of an organic ligand according to an embodiment of the present invention; Figure 2(b) schematically shows a structural diagram of an exemplified organic ligand according to an embodiment of the present invention.

[0064] In Figure 2(a), n = 1, 2, 3, 4, 5, 6, 7…; R = R1 = R2 = R3 = R4 = R5 = R6 = -OH, -COOH, -SO3H, -PO3H, -CHO, -H, -X, -NH2, -NO2, -CF3, -CN, -CH3, -OMe, etc. Each organic ligand has at least two oxygen-containing coordination sites. Figure 2(b) illustrates the structures of several exemplified organic ligands.

[0065] According to embodiments of the present invention, the acidic aqueous solution is prepared by mixing an acid activator with water. The acid activator may include inorganic acids or organic acids. Inorganic acids may include at least one of the following: hydrochloric acid, sulfuric acid, nitric acid, or phosphoric acid; organic acids may include at least one of the following: formic acid, acetic acid, oxalic acid, sulfonic acid, or phosphorous acid.

[0066] According to an embodiment of the present invention, mixing a solid titanium-containing compound precursor, an organic ligand, and an acidic aqueous solution in a certain proportion may include: stirring the above composition evenly at room temperature to obtain a mixed reaction system. It should be noted that no chemical reaction occurs during this stage.

[0067] According to embodiments of the present invention, the preset conditions may include preset reaction temperature, reaction time, and reaction concentration. Under the preset reaction conditions, a homogeneously mixed reaction system undergoes a reaction.

[0068] According to an embodiment of the present invention, the preset reaction temperature can be room temperature to 200°C, and is preferably 25°C, 50°C, 100°C, 150°C, or 200°C.

[0069] According to embodiments of the present invention, the reaction time can be 2 to 72 hours, preferably 2 hours, 12 hours, 24 hours, 36 hours, or 72 hours.

[0070] According to an embodiment of the present invention, the preset ratio can be: the molar ratio of the solid titanium-containing compound precursor to the organic ligand is 1:3 to 3:1; the molar ratio of the solid titanium-containing compound precursor to the acid activator in the acidic aqueous solution is 1:1 to 1:50.

[0071] According to embodiments of the present invention, the reaction process in which a homogeneous reaction system reacts under preset conditions may include three interrelated processes: the activation and slow release of titanium ions in the mixed reaction system, the coordination process of titanium ions with organic ligands, and the crystallization growth process of titanium-oxygen coordination products.

[0072] According to embodiments of the present invention, the activation and slow release process of titanium ions is mainly controlled by the reaction temperature and the molar ratio of the acid activator to the solid titanium-containing compound precursor.

[0073] According to embodiments of the present invention, the molar ratio of the solid titanium-containing compound precursor to the acid activator can be 1:1 to 1:50, and the reaction temperature can be room temperature to 200°C. The reaction temperature provides the driving force for the mixed reaction system and ensures the coordinated execution of the three related processes during the reaction. If the reaction temperature is too low, the reaction will not occur; if the reaction temperature is too high, the higher the concentration of the acid activator, the greater the activation and release rate of titanium ions from the solid titanium-containing compound precursor, and the greater the rate at which titanium ions hydrolyze into titanium dioxide precipitate. Therefore, a certain reaction temperature is required to avoid the formation of titanium dioxide precipitate in the mixed reaction system during the reaction process.

[0074] According to embodiments of the present invention, at a certain reaction temperature, in order to avoid the formation of titanium dioxide precipitate, the interaction rate between titanium ions and organic ligands must be greater than the rate of titanium ion hydrolysis to form titanium dioxide precipitate. This ensures that coordination remains dominant in competition with the hydrolysis reaction, thus driving the shift of reaction equilibrium. Therefore, a certain reaction temperature is required for the mixed reaction system to better achieve the second process of the reaction, namely, the competitive coordination between titanium ions and organic ligands.

[0075] However, in the traditional coordination synthesis of organic ligands with metal ions (e.g., titanium ions), low reaction concentrations, such as 0.001–0.01 mmol / mL, are generally used to reduce the probability of collisions between reactants, control the reaction rate, and thus ensure the growth of crystalline products. However, in aqueous phase reactions, these traditional coordination synthesis conditions cannot meet the competitive coordination requirements between titanium ions and organic ligands. The hydrolysis rate of titanium ions is much greater than the coordination reaction rate, making titanium dioxide precipitate the main reaction product.

[0076] According to embodiments of the present invention, a high reaction concentration condition, opposite to that of conventional coordination synthesis, can be used to increase the collision probability between the organic ligand and titanium ions. The high reaction concentration can be 0.1–5 mmol / mL. This high reaction concentration allows coordination to maintain a competitive advantage in the reaction, avoiding the formation of titanium dioxide precipitates.

[0077] Furthermore, since each organic ligand disperses differently in acidic aqueous solutions, each organic ligand has an optimal reaction concentration range to obtain a pure, highly crystalline product. Below this concentration range, effective collisions between the organic ligand and the solid titanium-containing compound precursor occur, resulting in a clear liquid or titanium dioxide precipitate; while above this concentration range, the organic ligand cannot react completely, leading to a complex product with low purity. Therefore, based on the efforts of those skilled in the art, this reaction concentration range can be 0.1–5 mmol / mL.

[0078] According to embodiments of the present invention, the competitive coordination between the organic ligand and the solid titanium-containing compound precursor can also be further adjusted by adjusting the molar ratio of titanium ions to organic ligands.

[0079] According to an embodiment of the present invention, the molar ratio of titanium ions to organic ligands can be 1:3 to 3:1, so that each organic ligand has a corresponding molar ratio with the corresponding solid titanium-containing compound precursor, so as to promote the reaction of the mixed reaction system to always move towards the equilibrium direction that is favorable to coordination, and ensure that a pure product is obtained; a molar ratio lower than this or higher than this molar ratio will result in the presence of impurities such as organic ligands or titanium dioxide in the product.

[0080] According to embodiments of the present invention, the crystallization growth of crystalline titanium-oxygen coordination products is the result of the combined effects of thermodynamics and kinetics. Excessive rates of competitive coordination can lead to overly rapid formation of coordination products, making it impossible to control the crystallization rate and resulting in products with poor crystallinity, small and uneven particles, or even amorphous / non-crystalline products. On the other hand, when the crystal structure of the titanium-oxygen coordination product reaches its lowest energy stable state, the complex chemical environment it inhabits can interfere with the long-range order of the crystal structure in subsequent reaction periods, such as crystal defects caused by coordination exchange and product destruction caused by titanium ion hydrolysis. Therefore, kinetic control through adjustment of reaction time is extremely important.

[0081] According to embodiments of the present invention, the reaction time of the mixed reaction system can be 2–72 h to control the kinetics of the mixed reaction system, thereby obtaining a titanium-oxygen coordination material with high crystallinity and excellent stability. Too short a reaction time will result in incomplete reaction, while too long a reaction time may not only damage the crystal structure of the crystalline coordination product but also significantly increase the energy consumption during the synthesis process.

[0082] According to embodiments of the present invention, the structures of the prepared titanium-oxygen coordination materials range from zero-dimensional to three-dimensional. Due to the introduction of organic ligands, the spatial dimensions of the structure can be continuously extended from unconnected zero-dimensional clusters to one-dimensional chains, two-dimensional layers, and three-dimensional structures.

[0083] According to embodiments of the present invention, by using water as the synthesis solvent, a solid titanium-containing compound precursor as the metal source, and utilizing in-situ acid activation of the titanium precursor, an unconventional high-concentration reaction is employed to prevent the hydrolysis of titanium ions, control the reaction rate, promote the formation of titanium-oxygen coordination materials, and balance the hydrolysis and coordination processes of titanium ions. This addresses the limitations of the range of factors controlling the chemical environment and spatial characteristics of the active sites in the material, as well as the technical problems in the preparation of traditional titanium-oxygen coordination materials, which are limited by the high reactivity and complexity of titanium ions in solution, leading to difficulties in reaction control and the easy formation of titanium dioxide precipitates, thus preventing the synthesis of highly crystalline titanium-oxygen coordination materials. This method achieves the preparation of novel zero- to three-dimensional titanium-oxygen coordination materials with high crystalline properties and superior chemical stability. Furthermore, the synergistic effect between each process of titanium-oxygen coordination is controlled by varying the reaction temperature, reaction time, and the molar ratio of the composition, simultaneously achieving the synthesis of novel titanium-oxygen coordination materials from both thermodynamic and kinetic perspectives, demonstrating the universality of this preparation method.

[0084] The present invention also provides a titanium-oxygen coordination material, which is prepared by the above-described preparation method.

[0085] This invention also provides an application of the titanium-oxygen coordination material in the fields of mixture adsorption and separation, catalysis, guest storage, proton conduction, response to external stimuli, and biomedicine.

[0086] To further understand the present invention, preferred embodiments are described below with reference to examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, and not for limiting the scope of the claims. All compositions used in the following examples are commercially available and have not undergone further purification.

[0087] Example 1

[0088] In a 25 mL round-bottom flask, 1 mmol of squaric acid was added to 10 mL of 3 M hydrochloric acid aqueous solution and stirred at room temperature. Then, 1 mmol of titanium oxysulfate was added to the solution and stirred until homogeneous, resulting in a mixed reaction system. This mixed reaction system was reacted under preset conditions: a reaction time of 24 h, a reaction concentration of 0.1 mmol / mL, and a reaction temperature of 120 °C. After the reaction was completed, the mixture was cooled to room temperature, and the resulting product was collected by filtration, washed, and dried to obtain the titanium-oxygen coordination material.

[0089] Figure 3(a) schematically shows a structural unit of the inorganic component of the titanium-oxygen coordination material according to Embodiment 1 of the present invention; Figure 3(b) schematically shows a structural schematic of the titanium-oxygen coordination material according to Embodiment 1 of the present invention; Figure 3(c) schematically shows a powder X-ray diffraction pattern of the titanium-oxygen coordination material according to Embodiment 1 of the present invention; Figure 3(d) schematically shows a scanning electron microscope image of the titanium-oxygen coordination material according to Embodiment 1 of the present invention; Figure 3(e) schematically shows a thermogravimetric analysis diagram of the titanium-oxygen coordination material according to Embodiment 1 of the present invention; Figure 3(f) schematically shows a carbon dioxide adsorption isotherm of the titanium-oxygen coordination material according to Embodiment 1 of the present invention.

[0090] As shown in Figure 3(a), the inorganic component structural unit of the titanium-oxygen coordination material in this embodiment is a continuous two-dimensional layer; as shown in Figure 3(b), the squaric acid organic ligand extends vertically between adjacent titanium-oxygen layers, using the four oxygen atoms of squaric acid to bridge the upper and lower pairs of Ti. 4+ The ions constitute the three-dimensional structure of the titanium-oxygen coordination material in this embodiment. As can be seen from Figure 3(c), the X-ray diffraction pattern of the titanium-oxygen coordination material in this embodiment shows that the obtained material has high crystallinity. As can be seen from Figure 3(d), the titanium-oxygen coordination material in this embodiment has a crystalline state, and the shape is relatively regular and the distribution is relatively uniform. As can be seen from Figure 3(e), the titanium-oxygen coordination material in this embodiment can be stabilized to the point where the maximum weight loss occurs at 300℃, indicating that the titanium-oxygen coordination material has excellent thermal stability. As can be seen from Figure 3(f), combined with the adsorption curve and adsorption amount of the titanium-oxygen coordination material in this embodiment, it can be shown that the titanium-oxygen coordination material in this embodiment has a confined space inside, that is, it has accessible pores (i.e., usable pores).

[0091] Example 2

[0092] In a 50 mL round-bottom flask, gallic acid (20 mmol) was added to a 20 mL solution of 3 M hydrochloric acid and stirred at room temperature. Then, titanium oxysulfate (20 mmol) was added to the solution and stirred until homogeneous to obtain a mixed reaction system. This mixed reaction system was reacted under preset conditions: a reaction time of 24 h, a reaction concentration of 1 mmol / mL, and a reaction temperature of 120 °C. After the reaction was completed, the mixture was cooled to room temperature, and the resulting product was collected by filtration, washed, and dried to obtain the titanium oxy coordination material.

[0093] Figure 4(a) schematically shows a structural unit of the inorganic component of the titanium-oxygen coordination material according to Embodiment 2 of the present invention; Figure 4(b) schematically shows a structural schematic of the titanium-oxygen coordination material according to Embodiment 2 of the present invention; Figure 4(c) schematically shows a powder X-ray diffraction pattern of the titanium-oxygen coordination material according to Embodiment 2 of the present invention; Figure 4(d) schematically shows a scanning electron microscope image of the titanium-oxygen coordination material according to Embodiment 2 of the present invention; Figure 4(e) schematically shows a thermogravimetric analysis diagram of the titanium-oxygen coordination material according to Embodiment 2 of the present invention; Figure 4(f) schematically shows a carbon dioxide adsorption isotherm of the titanium-oxygen coordination material according to Embodiment 2 of the present invention.

[0094] As can be seen from Figure 4(a), the inorganic component structural unit of the titanium-oxygen coordination material in this embodiment is a zero-dimensional cluster; as can be seen from Figure 4(b), the gallic acid linker utilizes two phenolic hydroxyl oxygens to connect two Ti atoms respectively. 4+ The unit utilizes the two oxygen atoms on the carboxyl group to connect a Ti atom. 4+ The unit forms a one-dimensional double-stranded chain structure; as shown in Figure 4(c), the X-ray diffraction pattern of the titanium-oxygen coordination material in this embodiment shows that the obtained material has high crystallinity; as shown in Figure 4(d), the titanium-oxygen coordination material in this embodiment has a crystalline state, and the shape is relatively regular and the distribution is relatively uniform; as shown in Figure 4(e), the titanium-oxygen coordination material in this embodiment can be stabilized to the point of maximum weight loss at 250℃, indicating that the titanium-oxygen coordination material has excellent thermal stability; as shown in Figure 4(f), combined with the adsorption curve and adsorption amount of the titanium-oxygen coordination material in this embodiment, it can be shown that the titanium-oxygen coordination material in this embodiment has a confined space inside, that is, it has accessible pores (i.e., usable pores).

[0095] Example 3

[0096] In a 50 mL round-bottom flask, pyromellitic acid (30 mmol) was added to a 3M hydrochloric acid aqueous solution (i.e., 20 mL), and stirred at room temperature. Then, titanium oxysulfate (30 mmol) was added to the above solution, and the mixture was stirred until homogeneous to obtain a mixed reaction system. This mixed reaction system was reacted under preset conditions of a reaction time of 24 h, a reaction concentration of 1.5 mmol / mL, and a reaction temperature of 120 °C. After the reaction was completed, the mixture was cooled to room temperature, and the resulting product was collected by filtration, washed, and dried to obtain the titanium oxy coordination material.

[0097] Figure 5(a) schematically shows a structural unit of the inorganic component of the titanium-oxygen coordination material according to Example 3 of the present invention; Figure 5(b) schematically shows a structural schematic of the titanium-oxygen coordination material according to Example 3 of the present invention; Figure 5(c) schematically shows a powder X-ray diffraction pattern of the titanium-oxygen coordination material according to Example 3 of the present invention; Figure 5(d) schematically shows a scanning electron microscope image of the titanium-oxygen coordination material according to Example 3 of the present invention; Figure 5(e) schematically shows a thermogravimetric analysis diagram of the titanium-oxygen coordination material according to Example 3 of the present invention; Figure 5(f) schematically shows a carbon dioxide adsorption isotherm of the titanium-oxygen coordination material according to Example 3 of the present invention.

[0098] As shown in Figure 5(a), the inorganic structural unit of the titanium-oxygen coordination material in this embodiment is a one-dimensional titanium-oxygen chain. As shown in Figure 5(b), adjacent titanium-oxygen chains are connected by four oxygen atoms of the two carboxyl groups on the pyromellitic acid linker, forming a three-dimensional structure of the titanium-oxygen coordination material. As shown in Figure 5(c), the X-ray diffraction pattern of the titanium-oxygen coordination material in this embodiment shows that the obtained material has high crystallinity. As shown in Figure 5(d), the titanium-oxygen coordination material in this embodiment is crystalline, with a relatively regular shape and uniform distribution. As shown in Figure 5(e), the titanium-oxygen coordination material in this embodiment can be stabilized to the point of maximum weight loss at 300℃, indicating that the titanium-oxygen coordination material has excellent thermal stability. As shown in Figure 5(f), combined with the adsorption curve and adsorption amount of the titanium-oxygen coordination material in this embodiment, it can be shown that the titanium-oxygen coordination material in this embodiment has a confined space inside, that is, it has accessible pores (i.e., usable pores).

[0099] Example 4

[0100] In a 50 mL round-bottom flask, 30 mmol of 1,2,4-benzenetricarboxylic acid was added to 20 mL of 3M hydrochloric acid aqueous solution and stirred at room temperature. Then, 30 mmol of titanium oxysulfate was added to the solution and stirred until homogeneous, resulting in a mixed reaction system. This mixed reaction system was reacted under preset conditions of 24 h, a reaction concentration of 1.5 mmol / mL, and a reaction temperature of 120 °C. After the reaction was completed, the mixture was cooled to room temperature, and the resulting product was collected by filtration, washed, and dried to obtain the titanium oxy coordination material.

[0101] Figure 6(a) schematically shows a structural unit of the inorganic component of the titanium-oxygen coordination material according to Embodiment 4 of the present invention; Figure 6(b) schematically shows a structural schematic of the titanium-oxygen coordination material according to Embodiment 4 of the present invention; Figure 6(c) schematically shows a powder X-ray diffraction pattern of the titanium-oxygen coordination material according to Embodiment 4 of the present invention; Figure 6(d) schematically shows a scanning electron microscope image of the titanium-oxygen coordination material according to Embodiment 4 of the present invention; Figure 6(e) schematically shows a thermogravimetric analysis diagram of the titanium-oxygen coordination material according to Embodiment 4 of the present invention; Figure 6(f) schematically shows a carbon dioxide adsorption isotherm of the titanium-oxygen coordination material according to Embodiment 4 of the present invention.

[0102] As shown in Figure 6(a), the inorganic component structural unit of the titanium-oxygen coordination material in this embodiment is a one-dimensional titanium-oxygen chain. As shown in Figure 6(b), the two oxygen atoms on a carboxyl group of 1,2,4-benzenetricarboxylic acid are respectively connected to two adjacent titanium atoms to form a one-dimensional chain structure. As shown in Figure 6(c), the X-ray diffraction pattern of the titanium-oxygen coordination material in this embodiment shows that the obtained material has high crystallinity. As shown in Figure 6(d), the titanium-oxygen coordination material in this embodiment is crystalline, with a relatively regular shape and uniform distribution. As shown in Figure 6(e), the titanium-oxygen coordination material in this embodiment can be stabilized to the point of maximum weight loss at 250℃, indicating that the titanium-oxygen coordination material has excellent stability. As shown in Figure 6(f), combined with the adsorption curve and adsorption amount of the titanium-oxygen coordination material in this embodiment, it can be shown that the titanium-oxygen coordination material in this embodiment has a confined space inside, that is, it has accessible pores (i.e., usable pores).

[0103] Example 5

[0104] In a 23 mL Teflon reactor, 7.5 mmol of 4,6-dihydroxyisophthalic acid was added to 10 mL of 3 M hydrochloric acid aqueous solution and stirred at room temperature. Then, 7.5 mmol of titanium oxysulfate was added to the solution and stirred until homogeneous, resulting in a mixed reaction system. This mixed reaction system was reacted under preset conditions: a reaction time of 72 h, a reaction concentration of 0.75 mmol / mL, and a reaction temperature of 120 °C. After the reaction was completed, the mixture was cooled to room temperature, and the resulting product was collected by filtration, washed, and dried to obtain the titanium-oxygen coordination material.

[0105] Figure 7(a) schematically shows a schematic diagram of the inorganic component structural unit of the titanium-oxygen coordination material according to Embodiment 5 of the present invention; Figure 7(b) schematically shows a schematic diagram of the structure of the titanium-oxygen coordination material according to Embodiment 5 of the present invention; Figure 7(c) schematically shows a powder X-ray diffraction pattern of the titanium-oxygen coordination material according to Embodiment 5 of the present invention; Figure 7(d) schematically shows a scanning electron microscope image of the titanium-oxygen coordination material according to Embodiment 5 of the present invention; Figure 7(e) schematically shows a thermogravimetric analysis diagram of the titanium-oxygen coordination material according to Embodiment 5 of the present invention; Figure 7(f) schematically shows a carbon dioxide adsorption isotherm of the titanium-oxygen coordination material according to Embodiment 5 of the present invention.

[0106] As shown in Figure 7(a), the inorganic component structural unit of the titanium-oxygen coordination material in this embodiment is a mononuclear titanium structural unit. As shown in Figure 7(b), the adjacent hydroxyl oxygen and one carboxyl oxygen on the two 4,6-dihydroxyisophthalic acid linkers form the equatorial plane, and the two μ2-OH are located at the vertical poles, forming a mononuclear structure. As shown in Figure 7(c), the X-ray diffraction pattern of the titanium-oxygen coordination material in this embodiment shows that the obtained material has high crystallinity. As shown in Figure 7(d), the titanium-oxygen coordination material in this embodiment is crystalline, with a relatively regular shape and a relatively uniform distribution. As shown in Figure 7(e), the titanium-oxygen coordination material in this embodiment can be stabilized to the point of maximum weight loss at 200℃, indicating that the titanium-oxygen coordination material has excellent thermal stability. As shown in Figure 7(f), combined with the adsorption curve and adsorption amount of the titanium-oxygen coordination material in this embodiment, it can be shown that the titanium-oxygen coordination material in this embodiment has a confined space inside, that is, it has accessible pores (i.e., usable pores).

[0107] In summary, as can be seen from the schematic diagrams of the inorganic component structural units in each embodiment, titanium-oxygen coordination materials can be prepared using inorganic structural units ranging from zero-dimensional to two-dimensional, and the resulting materials have zero-dimensional to three-dimensional structures. The adsorption curves of each embodiment show that the titanium-oxygen coordination materials prepared in each embodiment all have accessible pores. The X-ray diffraction patterns of each embodiment show that the titanium-oxygen coordination materials prepared in each embodiment all have high crystallinity. The thermogravimetric analysis diagrams of each embodiment show that the titanium-oxygen coordination materials prepared in each embodiment all have excellent thermal stability. The scanning electron microscope images of each embodiment show that the titanium-oxygen coordination materials prepared in each embodiment are crystalline, and the distribution of each structure of the titanium-oxygen coordination material is relatively uniform and the shape is regular.

[0108] The above specific embodiments further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above are merely specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a titanium-oxygen coordination material, comprising: A solid titanium-containing compound precursor, an organic ligand, and an acidic aqueous solution are mixed in a predetermined ratio to obtain a mixed reaction system. The organic ligand is an organic compound having two or more oxygen coordination sites. The acidic aqueous solution is prepared by mixing an acid activator with water. The solid titanium-containing compound precursor is a solid titanium-containing element compound selected from titanium complexes. The parent structure of the organic ligand includes at least one of the following: an aliphatic ring or an aromatic hydrocarbon. The coordinating group of the organic ligand includes at least one of the following: a carboxyl group or a hydroxyl group. The mixed reaction system reacts under preset conditions to generate titanium-oxygen coordination materials; The structure of the titanium-oxygen coordination material includes zero-dimensional to three-dimensional components; the molar ratio of the solid titanium-containing compound precursor to the organic ligand is 1:3 to 3:1; the molar ratio of the solid titanium-containing compound precursor to the acid activator is 1:1 to 1:5; the preset conditions include: a reaction concentration of 0.1 to 5 mmol / mL; a reaction time of 2 to 72 h; and a reaction temperature of room temperature to 200 °C.

2. The method according to claim 1, wherein, The acid activator includes inorganic or organic acids, wherein the inorganic acid includes at least one of the following: hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, or phosphorous acid, and the organic acid includes at least one of the following: formic acid, acetic acid, oxalic acid, or sulfonic acid.

3. The method according to claim 1, wherein, The reaction process of the mixed reaction system under preset conditions includes: activation and slow release of titanium ions in the mixed reaction system, coordination of the titanium ions with the organic ligand, and crystal growth of the titanium-oxygen coordination product.

4. A titanium-oxygen coordination material prepared by the preparation method according to any one of claims 1 to 3.

5. An application of the titanium-oxygen coordination material as described in claim 4 in the field of carbon dioxide adsorption.

Citation Information

Patent Citations

  • Organic titanium phosphonate crystalline porous material, preparation method thereof and application of organic titanium phosphonate crystalline porous material to filter column

    CN114316283A

  • Spherical crystalline powder of titanium oxyoxalate, and method for producing the same

    JP2011132129A